Petrographic and geochemical characterisation of the hangingwall and the footwall rocks (the Dipeta and R.A.T. stratigraphic units) to the Kinsevere and Nambulwa copper ore deposits of the Lufilian Arc, southern Democratic Republic of Congo - Nkulu, Robert Kankomba (Rhodes University, Faculty of Science, Department of Geology, 2020)
The Kinsevere and Nambulwa copper deposits in the Democratic Republic of Congo (D.R.C.) are set in the eastern side of the Neoproterozoic Katanga Supergroup, forming the Lufilian Arc, resulting from a cratonic collision between the Congo and the Kalahari Cratons (ca.620-570_Ma). The Katanga Supergroup was deposited in an extensional rift setting with a sedimentary thickness succession ranging between 7 to 10 km, sub-divided into: âˆ’ the Roan, the Nguba and the Kundelungu Groups. The stratigraphic column of the Roan Group consists of the R.A.T. (Roche Argilo Talqueuse), the Mines, the Dipeta and the Mwashya Subgroups. Three major deformation phases have been described characterised by complex multiphase tectonics related to a curved superposition of folded, thrust and sheared blocks. The rocks of the R.A.T., Mines and Dipeta Subgroups are recognised as blocks that occur within a stratiform to discordant and diapiritic megabreccia. The blocks were rafted upward with salt tectonics, resulting in the juxtaposition with the hangingwall and the footwall terranes. Therefore, in that context it has been found that the Dipeta may appear overlying the R.A.T. Subgroup through the unconformity decollement surface of heterogeneous breccia. The petrographic observations made of the R.A.T. and Dipeta samples indicates in both units the presence of detrital quartz and feldspar that have been altered and replaced by sericite and muscovite minerals. Gypsum is intimately associated with magnesite, showing an evaporitic environment domain, while magnesite is common as alteration phase both in the R.A.T. and Dipeta Subgroups. Pyrophyllite has been observed in the Dipeta, resulting from reaction of silica with the Kaolinite at low temperature. Accessory detrital minerals include zircon, as well as xenotime intergrown with altered Fe-Ti-oxide hematite, forming complex textures with disseminated Ti-oxides both in R.A.T. and Dipeta units. Major and trace element geochemistry indicates that the Dipeta is more dolomitic and magnesite while the R.A.T. is clay-rich. The Ti2O value of Dipeta and R.A.T samples is relatively low, ranging between 0.36 and 0.69 wt.% respectively, which suggest highly evolved felsic material in the protolith. This is consistent with interpretation based on the Al2O3/TiO2 ratio, which ranges between 18 and 23 for the R.A.T. and Dipeta respectively, indicating an intermediate to felsic granitoids as the protolith of R.A.T. and Dipeta siltstones. The Ti/Zr ratio of R.A.T. and Dipeta samples of less than 10, while, the higher La/Sc ratio of between 2.6 and 5.5 (for the R.A.T. and Dipeta respectively) indicate that both the R.A.T. and Dipeta are active continental and passive margin tectonic setting. Based on the geochemical variation with depth across the R.A.T. and Dipeta and their contact zone, a geochemical fingerprinting suggests that the ratio TiO2/Al2O3 appears to be useful and could be considered as a stratigraphic geochemical maker able to discriminate the R.A.T. and the Dipeta Subgroups during the geological mapping.
Keywords: Petrogenesis -- Congo (Democratic Republic); Analytical geochemistry -- Congo (Democratic Republic); Copper ores -- Congo (Democratic Republic); Ore deposits -- Congo (Democratic Republic); Katangan Sequence; Geological mapping -- Congo (Democratic Republic); Central African Copperbelt (Congo and Zambia); Lufilian Arc; Neoproterozoic Katangan R.A.T. (Roches Argilo Talqueuse) Subgroup; Dipeta Subgroup